Managing School Resources and Financial Competencies of Secondary School Administrators in the Delivery of Basic Education Services - Hernandez, Melanie P. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
In order to improve school performance, school leaders must be more effective and efficient in their administration, and their management skills must be enhanced. As a result, this study aimed to determine if there was a link between school administrators’ financial competencies in managing school resources and the financial management practices of the Schools Division of Quezon. The descriptive-correlational technique of research was used to conduct the study with 372 school administrators and teachers in the Division of Quezon to analyze the link between the independent and dependent variables. Descriptive and Inferential analyses were carried out using SPSS. The findings revealed that managing school resources was highly practiced by the respondents, such as record management, financial management, school facilities and equipment, staff management, and school safety for disasters. In terms of financial management, the respondents highly practiced budgeting, auditing, finance and resource management mobilization, financial reporting, and inventory management. On matters of school administrators’ financial management, the respondents were highly competent in the areas of securing financial resources, fiscal management, the use of technology in the management of operations, coordinating with others, and professionalism. Furthermore, the result confirmed the significant correlation between the financial management competencies of the school administrators in managing school resources and financial management practices. Also, there were single and combined related variables of financial management competencies that demonstrated significant effects and served as predictors for managing school resources and financial management. Annual orientation, seminars, and workshops for school administrators in SDO Quezon on financial management, technology, awareness, codes, facilities, and professional development improve performance. Technical help, mentorship, and benchmarking are also essential.